Prospective clinical investigation of the relationship between idiopathic benign paroxysmal positional vertigo and bone turnover: A pilot study. (14th May 2013) - Parham, Kourosh; Leonard, Gerald; Feinn, Richard S.; Lafreniere, Denis; Kenny, Anne M.
Abstract : Objective/Hypothesis: Idiopathic benign paroxysmal positional vertigo (BPPV) is a strong indicator of decreased bone density (osteopenia/osteoporosis) in postmenopausal women, and there is a correlation between BPPV and serum levels of biochemical markers of bone turnover. Study Design: Prospective pilot clinical trial. Methods: Two groups of postmenopausal women were recruited. The BPPV group consisted of 16 women with a diagnosis of BPPV. The OSTEO group consisted of 13 women with history of osteopenia/osteoporosis. Dual‐energy x‐ray absorptiometry scan results were compared, along with serum levels of ionized calcium (iCa), vitamin D, aminoterminal propeptide of protocollagen type I (P1NP), and aminoterminal telopeptides of collagen (sNTX). Results: Prevalence of decreased bone mass density among BPPV subjects was 81%, and prevalence of BPPV among OSTEO subjects was 31%. BPPV subjects had higher P1NP levels. Multiple regression analysis showed that among BPPV subjects, there was positive correlation between P1NP and sNTX and a negative correlation between P1NP and vitamin D level. Age was positively correlated with serum levels of both biomarkers among the BPPV subjects. T score, serum iCa, and serum vitamin D levels did not appear to correlate with presence of BPPV. Conclusions: Idiopathic BPPV subjects have a high prevalence of osteopenia/osteoporosis. Levels of biochemical markers of bone turnover correlate with presence of BPPV. Our results, based on a sample of U.S. subjects, support an association between idiopathic BPPV and disorders of bone turnover. Level of Evidence: 2b. Laryngoscope, 123:2834–2839, 2013